Digital logic and knowledge-based system for the automotive piston material selection - Maleque, Md. Abdul; Arifutzzaman, A. (Inderscience Enterprises Ltd., 2012)
The aim of this paper is to apply material selection methods for selecting the most appropriate material for piston application. Initial candidate materials such as, grey cast iron, Ti and Al alloys, 20% SiC reinforced Al and Al-Cu alloy matrix composites and WC-TiC reinforced Ti matrix composite were analysed based on their performance requirements. Digital logic (DL) approach was implemented for material selection and knowledge-based system (KBS) was used for comparison purposes. In DL method, performance index (PI) was measured using the scaled property and weighting factor. The figure of merit was obtained based on PI and relative cost of each candidate material. In KBS, a MATLAB network tool was employed for comparison purposes. The highest PI was found for 20% SiC reinforced Al-Cu alloy composite compared to other materials and hence can be selected for the new generation automotive piston application.